Review of the Banking Sector Profit Persistence - Abel, Sanderson; Hlalefang, Khobai; Le Roux, Pierre; Mutandwa, Learnmore (International Journal of Economics and Financial Issues, 2018)
The study aims to investigate the profit persistence and identify the determinants of profitability in the Zimbabwean banking sector during the period 2009-2014. The study established that banks were inefficient operating under monopolistic competition. The study revealed that profitability does not persist implying banks are enjoying abnormal profits over time. The results further reveals that market power, cost efficiency, credit risk, liquidity risk and the size of the bank are significant factors influencing bank profits. The results indicate that bank profits are determined mostly by strategies adopted by bank management. Keywords: Competition, Generalised Methods of moment, Instrumental Variables, Persistence, Profitability. JEL Classifications: L25, G21, C33